Pemberdayaan Masyarakat Melalui Inovasi Lilin Aromaterapi Berbahan Minyak Jelantah untuk Pengelolaan Limbah Rumah Tangga di Kelurahan Tettikenrarae, Kec. Marioriwawo, Kab. SOPPENG - Abdurahman Hamid; Siti Nur Rahmi Gani_; Nurazizah Nurdin; A. Achmad Ibrahim; Syahrullah Asyari (LPP Chani, 2026)
Waste cooking oil is one of the most common household residues that often causes environmental pollution when improperly disposed of into waterways or soil. This problem is also found in Tettikenrarae Village, Marioriwawo District, Soppeng Regency. This Community Service Program (KKN) aimed to empower the local community by introducing an innovation to recycle used cooking oil into eco-friendly and economically valuable aromatherapy candles. The program was conducted through socialization and hands-on training, involving residents in each stage of candle-making, from preparing the materials, mixing, to molding the products. The results indicated an improvement in participants’ knowledge and skills in processing household waste into useful products. Moreover, the community became more aware of the circular economy potential through creative products that can be marketed. This activity is expected to serve as an initial step toward sustainable waste management and to create opportunities for small-scale environmentally friendly businesses in the local area.